2020
DOI: 10.3390/jof6020065
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Antimicrobial Peptides and Proteins against Aspergillus fumigatus

Abstract: Antimicrobial peptides and proteins (AMPs) provide an important line of defence against invading microorganisms. However, the activity of AMPs against the human fungal pathogen Aspergillus fumigatus remains poorly understood. Therefore, the aim of this study was to characterise the anti-Aspergillus activity of specific human AMPs, and to determine whether A. fumigatus can possess resistance to specific AMPs, as a result of in-host adaptation. AMPs were tested against a wide range of clinical isolates of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 59 publications
(62 reference statements)
4
29
2
Order By: Relevance
“…Ballard et al. (2020) ( Ballard et al., 2020 ) demonstrated that lysozyme and histones inhibited hyphal metabolic activity in A. fumigatus isolates in a dose-dependent manner, and imaging flow cytometry revealed that histones inhibited the germination of A. fumigatus conidia. Recently, it was demonstrated that histone H2A enters Escherichia coli and S. aureus through membrane pores formed by the AMPs LL-37 and magainin-2, depolarizing the bacterial membrane potential, and impairing membrane recovery ( Doolin et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ballard et al. (2020) ( Ballard et al., 2020 ) demonstrated that lysozyme and histones inhibited hyphal metabolic activity in A. fumigatus isolates in a dose-dependent manner, and imaging flow cytometry revealed that histones inhibited the germination of A. fumigatus conidia. Recently, it was demonstrated that histone H2A enters Escherichia coli and S. aureus through membrane pores formed by the AMPs LL-37 and magainin-2, depolarizing the bacterial membrane potential, and impairing membrane recovery ( Doolin et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much of our current study has centered around the role of an early ROS burst in response to A. fumigatus that is dependent on Nlrx1. However, it is critical to acknowledge a number of additional non-oxidative defense strategies such as secreted peptides and proteins (47)(48)(49) may also be differentially expressed in a decreasing manner in the Nlrx1-deficient background. One broad conclusion of our study is that the functions and roles of Nlrx1 continue to extend, and these processes, such as an absence of negative regulation of glycolysis may also impact additional processes within the cell such as gene expression of defense proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, further in vivo investigations are needed regarding LL-37 cytotoxicity on mammalian cells to be a potential drug candidate for combating C. auris infections ( Rather et al, 2022 ). Unfortunately, controversial results have been reported for LL-37 activity in case of Aspergillus species ( Luo et al, 2019 ; Ballard et al, 2020 ), however, cathelicin-based synthesized peptides seem to be promising antifungals against A. fumigatus ( van Eijk et al, 2020 ).…”
Section: Peptides With Antifungal Activity As Potential Therapeutic A...mentioning
confidence: 99%